Fearless Fighters and Submissive Wives: Negotiating Identity among Women Soldiers in the Congo (DRC). (October 2013) - Baaz, Maria Eriksson; Stern, Maria
This article addresses an underreported aspect of contemporary warring in the Democratic Republic of Congo (DRC): the experiences of women soldiers and officers in the Congolese national armed forces (Forces Armées de la République Démocratique du Congo [FARDC]). It thus addresses an empirical gap in scholarly and policy knowledge about female soldiers in national armies on the African continent, and the DRC in particular. Based on original interviews, the article explores the way female soldiers in the FARDC understand their identities as "women soldiers" and offers new insight into women soldiers' role and responsibilities in the widespread violence committed against civilians in the DRC. Moreover, it explores how their understanding of themselves as "women soldiers" both challenges and confirms familiar notions of the army as a masculine sphere. Such insight is important for better understanding the gendered makeup of the military and for contributing to a knowledge base for Security Sector Reform in this violent (post)conflict setting.